1989
DOI: 10.1128/aem.55.2.360-365.1989
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an Escherichia coli-Clostridium perfringens shuttle vector and plasmid transformation of Clostridium perfringens

Abstract: A stable shuttle vector which replicates in Escherichia coli and Clostridium perfringens was constructed by ligating a 3.6-kilobase (kb) fragment of plasmid pBR322 with C. perfringens plasmid plB101 (3.1 kb). The marker for this shuttle plasmid originated from the 1.3-kb chloramphenicol resistance gene of plasmid pHR106. The resulting shuttle vector, designated pAK201, is 8 kb in size and codes for resistance to 20 ,ug of chloramphenicol per ml in both E. coli and C. perfringens. Following shuttle vector const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Gels were calibrated using concatemerized lambda DNA or yeast chromosomes as markers then processed for Southern blotting using Hybond C-extra membranes (Amersham) as outlined (Canard and Cole, 1989). Plasmid DNA was prepared from fresh overnight cultures of certain strains by the method of Kim and Blaschek (1989) involving alkaline lysis followed by caesium chloride gradient eentrifugation. The following probes were labelled with [^^P]-dCTP by nick translation or random priming (Sambrook et al.…”
Section: Nucleic Acid Techniquesmentioning
confidence: 99%
“…Gels were calibrated using concatemerized lambda DNA or yeast chromosomes as markers then processed for Southern blotting using Hybond C-extra membranes (Amersham) as outlined (Canard and Cole, 1989). Plasmid DNA was prepared from fresh overnight cultures of certain strains by the method of Kim and Blaschek (1989) involving alkaline lysis followed by caesium chloride gradient eentrifugation. The following probes were labelled with [^^P]-dCTP by nick translation or random priming (Sambrook et al.…”
Section: Nucleic Acid Techniquesmentioning
confidence: 99%
“…This transformation method is currently proving widely applicable to many different bacterial genera [42,43]. Reports of transformation of intact cells of C. acetobutylicum NCIB 8052 [36] and C. perfringens [40,41] with various plasmids have already appeared (Table 3) and doubtless other species of Clostridium will be added to the list in the very near future.…”
Section: Transformation Of Whole Cells By Electroporationmentioning
confidence: 99%
“…Among these are those reported by Squires et al [27], based on small indigenous C. perfringens plasmids into which a Tc R gene from pCW3 was incorporated; refined derivatives containing a multiple cloning site and a Cm R gene from plasmid pJIR62 instead of the Tc R gene originally present have also been constructed [39]. Kim and Blaschek [41] have recently described a vector, pAK201, based on the small caseinase plasmid, pHB101, and the Cm R gene of Tn4451 (piP401).…”
Section: Indigenous Clostridial Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it was reported that only 44% of transformants containing the pMTL500 vector were resistant to erythromycin following 20 generations of subculture (N. Minton, Clostridium III). Clostridial vector constructs based on native DNA are expected to result in more stable genetic systems [21].…”
Section: Avail ~ \ Hindlll Bamhi T ~ Hpalmentioning
confidence: 99%